Building a mature UK trade policy - David Henig (European Centre for International Political Economy (ECIPE), 2023)
Global Britain has not delivered according to the hopes expressed by supporters of leaving the EU. Trade with the rest of the world has not grown to make up for leaving a bloc with seamless trade, early Free Trade Agreements with Australia and New Zealand are of minor economic significance, and it is hard to discern much of a strategy beyond completing a few more similar deals. Meanwhile the world of trade policy is transformed since 2016, negatively. The US has essentially declared its national interests to be more important than global rules, while the EU wants to act unilaterally as the global regulator. In both, the climate crisis is being used as an excuse to reintroduce protectionist measures threatening economic damage and global stability.
Keywords: 330; Außenwirtschaftspolitik; Großbritannien